2007
DOI: 10.1002/pds.1507
|View full text |Cite|
|
Sign up to set email alerts
|

Screening statins for possible carcinogenic risk: up to 9 years of follow‐up of 361 859 recipients

Abstract: Overall this study provided no strong evidence of either causation or prevention of cancer by statins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
233
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(248 citation statements)
references
References 41 publications
12
233
2
1
Order By: Relevance
“…Moyad et al (56) Why a statin and/or another proven In this follow-up manuscript, the authors argue the heart healthy agent should be utilized in the next need to conduct statin chemopreventive trials within major cancer chemoprevention trial: part II. (59) Screening statins for possible carcinogenic risk: Overall this study provided no strong evidence up to 9 years of follow-up of 361,859 recipients.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Moyad et al (56) Why a statin and/or another proven In this follow-up manuscript, the authors argue the heart healthy agent should be utilized in the next need to conduct statin chemopreventive trials within major cancer chemoprevention trial: part II. (59) Screening statins for possible carcinogenic risk: Overall this study provided no strong evidence up to 9 years of follow-up of 361,859 recipients.…”
Section: Resultsmentioning
confidence: 84%
“…A meta-analysis of 6 randomised control trials and 13 observational studies revealed a statistically significant inverse relationship between statin use and advanced disease, but not overall risk of developing prostate cancer (28). Among statin users, there has been observed a decreased risk in stage II prostate cancer (59). There was a trend towards a risk reduction for metastatic and fatal disease (16,60,61).…”
Section: Resultsmentioning
confidence: 99%
“…The magnitude of this negative association was similar for time periods extending beyond one year. When statin use and cancer development was accessed through a health care program database from northern Calofornia, esophageal carcinoma was more common among statin users [113] . Population studies published today, although they have been adjusted for many covariates including age, body mass index, smoking, do not differentiate between EAC and squamous carcinomas and do not allow evaluation of statin use in EAC prevention.…”
Section: Statins and Eac Chemopreventionmentioning
confidence: 99%
“…Some data exist for a decreased risk of melanoma with long-term (>5 years) use of cholesterol-lowering drugs in analysis of the Cancer Prevention Study II Nutritional Cohort from 1997-2007 (Jacobs et al, 2011), and higher doses of statin medications were associated with decreased melanoma risk upon analysis of a Vetaran's Administration pharmacy database (Farwell et al, 2008). However, the effect of long-term statin use on melanoma risk was not evident upon analysis of the Kaiser Permanente database (Friedman et al, 2008). Female sex hormones and oral contraceptive use have been called into question regarding a potential increased risk of melanoma, given the slightly higher risk of breast cancer patients for melanoma (Levi et al, 2003), and the fact that estrogens can increase melanocyte counts and cause cutaneous hyperpigmentation.…”
Section: Medicationsmentioning
confidence: 99%